Integrating social and value dimensions into sustainability assessment of lignocellulosic biofuels. (November 2015) - Raman, Sujatha; Mohr, Alison; Helliwell, Richard; Ribeiro, Barbara; Shortall, Orla; Smith, Robert; Millar, Kate
Abstract: The paper clarifies the social and value dimensions for integrated sustainability assessments of lignocellulosic biofuels. We develop a responsible innovation approach, looking at technology impacts and implementation challenges, assumptions and value conflicts influencing how impacts are identified and assessed, and different visions for future development. We identify three distinct value-based visions. From a techno-economic perspective, lignocellulosic biofuels can contribute to energy security with improved GHG implications and fewer sustainability problems than fossil fuels and first-generation biofuels, especially when biomass is domestically sourced. From socio-economic and cultural-economic perspectives, there are concerns about the capacity to support UK-sourced feedstocks in a global agri-economy, difficulties monitoring large-scale supply chains and their potential for distributing impacts unfairly, and tensions between domestic sourcing and established legacies of farming. To respond to these concerns, we identify the potential for moving away from a one-size-fits-all biofuel/biorefinery model to regionally-tailored bioenergy configurations that might lower large-scale uses of land for meat, reduce monocultures and fossil-energy needs of farming and diversify business models. These configurations could explore ways of reconciling some conflicts between food, fuel and feed (by mixing feed crops with lignocellulosic material for fuel, combining livestock grazing with energy crops, or using crops such as miscanthus to manage land that is no longer arable); different bioenergy applications (with on-farm use of feedstocks for heat and power and for commercial biofuel production); and climate change objectives and pressures on farming. Findings are based on stakeholder interviews, literature synthesis and discussions with an expert advisory group. Highlights: We develop a responsible innovation approach to assessing lignocellulosic biofuel systems. We clarify social and value dimensions required for integrated sustainability assessment. Insights on farming and agricultural system perspectives are important for sustainability assessment. We identify techno-economic, socio-economic and cultural-economic perspectives on lignocellulosic biofuel development. Regionally-tailored bioenergy configurations may provide alternatives to large-scale biorefinery models.